Support Desired by Women Following Termination of Pregnancy for a Fetal Anomaly. Issue 6 (2nd April 2015) - Ramdaney, Aarti; Hashmi, Syed S.; Monga, Manju; Carter, Rebecca; Czerwinski, Jennifer
Abstract: With the rapidly evolving field of prenatal testing, there is a growing need to provide support for women pursuing termination of pregnancy following the discovery of a fetal anomaly. Previous studies have documented that women in this situation often feel unsupported, but the type of resources desired by this population remains undetermined. We studied the awareness and utilization of support resources in 51 women at the time of the procedure, at 6 weeks, and at 3 months following the event. Though largely knowledgeable of existing resources at the time of the procedure, only 50 % admitted contemplating their individualized need for support. Most expected to rely on the support of family and friends. Additionally, 50 % expressed the desire to commemorate the pregnancy, though none wanted direct contact with their healthcare provider(s). Responses from the 6 weeks and 3 months assessments were consistent with previous literature as many women indicated not coping as expected and were unprepared for the psychological consequences following the procedure. Our findings indicate that women in these situations may not realize what their long‐term support needs will be. They further indicate that guidelines for routine follow‐up care should be established among healthcare providers that respect this population's initial desires to avoid reminders of the pregnancy and promote a flexible timeframe for support uptake. Additional support resources that promote flexible uptake as well as meet the desires of anonymity and ease of access need to be developed for this population.